Orthognathic Surgery in Patients With Cleidocranial Dysplasia - Conceicao Madeira, Maria Fernanda; Caetano, Isabela Maria; Dias-Ribeiro, Eduardo [UNESP]; Rocha, Julierme Ferreira [UNESP]; Sonoda, Celso Koogi [UNESP]; Sant'Ana, Eduardo; Faria Yaedu, Renato Yassutaka (Lippincott Williams &wilkins, 2015)
The aim of this study was to report the orthodontic-surgical approach of a 21-year-old female patient diagnosed with cleidocranial dysplasia. An orthognathic surgery was performed in the maxilla and mandible during the same procedure to correct an existing dentofacial deformity (class III malocclusion). In addition, malar prostheses were used to correct midface deficiency. After surgical intervention, orthodontic treatment continued in order to promote stability, function, and aesthetics. Cases of cleidocranial dysplasia treated with the defined criteria can bring aesthetic and functional benefits to the patient.
Keywords: Cleidocranial dysplasia; orthodontics; orthognathic surgery; mandibular advancement